Literature review of participatory measurement, reporting and verification (PMRV) - Hawthorne, S.D.; Boissiere, M. (Center for International Forestry Research, 2014)
We conducted a literature review of participatory monitoring and existing PMRV approaches to identify strategies and conditions that support the development and implementation of sustainable PMRV in the REDD+ context. To identify data and processes that should be included in PMRV, we reviewed MRV requirements in the REDD+ context. The literature is analyzed to summarize the lessons learned from participatory monitoring, examine when, where and how PMRV has been developed and implemented, and identify any knowledge gaps. With Indonesia as our case study, we explored the feasibility of PMRV implementation and assessed how PMRV could be integrated into the national MRV system. We examined the proposed national MRV system in Indonesia, compiled a database of REDD+ projects and conducted short interviews with selected project proponents.